Correlation Between CHA2DS2-VASc Score and Left Atrial Size in Patients With Atrial Fibrillation: A More Than 15-Year Prospective Follow-Up Study - Tsai, Chin-Feng; Huang, Pang-Shuo; Chen, Jien-Jiun; Chang, Sheng-Nan; Chiu, Fu-Chun; Lin, Ting-Tse; Lai, Ling-Ping; Hwang, Juey-Jen; Tsai, Chia-Ti (Frontiers in Cardiovascular Medicine, 2021)
Background Left atrial (LA) size represents atrial fibrillation (AF) burden and has been shown to be a predictor for AF stroke. CHA2DS2-VASc score is also a well-established predictor of AF stroke. It is unknown whether these two risk scores are correlated and whether both are independent predictors and complimentary to each other, or one of them is a major determinant of stroke risk for AF patients. Method A total of 708 patients from the National Taiwan University Atrial Fibrillation Registry were longitudinally followed up for more than 10 years. Left atrial size was measured by M mode of echocardiography. Adverse thromboembolic endpoints during follow-up were defined as ischemic stroke or transient ischemic accident. Results Both LA size and CHA2DS2-VASc score were associated with the risk of stroke in univariate analyses (c statistic 0.662 [0.601 to 0.723] for CHA2DS2-VASc score and 0.595 [0.516 to 0.674] for LA size). There was a positive correlation between LA size and CHA2DS2-VASc score (r=0.17, P<0.0001). Patients with higher CHA2DS2-VASc scores had a higher mean LA size (P<0.01 for trend). When combining LA size and CHA2DS2-VASc score in the multivariate Cox model, only CHA2DS2-VASc score remained statistically significant (HR 1.39 [1.20-1.63]; P<0.001). Conclusion There is a positive correlation between echocardiographic LA size and CHA2DS2-VASc score. LA size is not an independent predictor of AF stroke, but provides a diagnostic value to predict stroke risk. Calculation of CHA2DS2-VASc score may replace measurement of echocardiographic LA size when evaluating the risk of stroke for AF patients.